2020
DOI: 10.3390/ani10112136
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Emotional Connection with Pets: A Descriptive Analysis from Puerto Rico

Abstract: The study of human–animal interactions has become a prominent research field. The presence of pets in our daily lives has meant a change in the perception of our relationship with pets. One of the new lines of research that has opened up in this area analyzes the possible physical, emotional, and psychological benefits of a human–animal bond. In this context, two main objectives were pursued in this study, whose sample (N = 1436) was investigated in Puerto Rico: (PO1) determining the characteristics of the own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Social interactions with animals are highly emotionally relevant for a majority of people [7,[31][32][33][34]. We thus hypothesize that interacting with the dog led to higher emotional involvement in the participants compared to interacting with the plush animal.…”
Section: Hypothesis About Underlying Mechanismsmentioning
confidence: 94%
See 1 more Smart Citation
“…Social interactions with animals are highly emotionally relevant for a majority of people [7,[31][32][33][34]. We thus hypothesize that interacting with the dog led to higher emotional involvement in the participants compared to interacting with the plush animal.…”
Section: Hypothesis About Underlying Mechanismsmentioning
confidence: 94%
“…Interacting with an animal is a social situation that is emotionally relevant to most people [7,[31][32][33][34]. Several reviews have identified the prefrontal cortex as the key region for different aspects of social cognitive processing, such as theory of mind/mentalizing [35] and understanding self and others [36].…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen ( N = 19) volunteer dog owners (17 females, 2 males, age: M = 33 years) were chosen to participate in the study. The most common breeds were Border Collie ( 3 ), Labrador Retriever ( 3 ), mixed breed ( 2 ), and the rest included, for example, Welsh Springer Spaniel, Golden Retriever, Nova Scotia Duck Tolling Retriever, Australian Shepherd, Doberman, and German Shepherd. Six of the dogs were males, and the rest ( 12 ) were females.…”
Section: Methodsmentioning
confidence: 99%
“…Domestic dogs are highly social animals, and due to that, mutual relationships develop easily with humans ( 1 ). In Finland, as in many other cultures around the world ( 2 , 3 ), domestic dogs are considered as family members, who usually live at the homes of their owners. The strong social bond between dogs and their owners resembles the attachment between a parent and a child, and includes characteristics present in a friendship [reviewed in ( 4 )].…”
Section: Introductionmentioning
confidence: 99%
“…Based on Ursula Aragunde-Kohl's research, the coexistence of pets and humans is a continuously improving research field, and it has covered many scientific fields. Moreover, according to the results of Aragunde-Kohl's research, pets could have a positive impact on their owners' mental health with emotional connection, including the feelings of joy, peace and love [2]. However, there are two problems in the research.…”
Section: Introductionmentioning
confidence: 99%